1992
DOI: 10.1073/pnas.89.13.6085
|View full text |Cite
|
Sign up to set email alerts
|

High rates of Ac/Ds germinal transposition in Arabidopsis suitable for gene isolation by insertional mutagenesis.

Abstract: Overexpression of the Activator (Ac) transposase gene in Arabidopsis thaliana resulted in a minimal germinal transposition frequency of 27% in which independent Dissociation (Ds) transposition events were observed. Molecular analysis of 45 F1 generation AciDs plants indicated that high rates of somatic excision had occurred, and independent germinal insertions were identified in F2 generation progeny plants. A tandem cauliflower mosaic virus (CaMV) promoter fused to two different Ac coding sequences signifcant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 38 publications
3
46
0
1
Order By: Relevance
“…The assay relied on measuring restoration of GUS activity in the protoplast population. Using the same histochemical test, Becker et al (1992) recently identified more active ORFa constructs: the most active Ac was engineered so that the ORF starts at the 10th ATG. With this construct, the frequency of Ds excision was high even when the ORF was driven by the native Ac promoter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The assay relied on measuring restoration of GUS activity in the protoplast population. Using the same histochemical test, Becker et al (1992) recently identified more active ORFa constructs: the most active Ac was engineered so that the ORF starts at the 10th ATG. With this construct, the frequency of Ds excision was high even when the ORF was driven by the native Ac promoter.…”
Section: Discussionmentioning
confidence: 99%
“…One million N. plumbaginifo/ia protoplasts were transformed with 10 I~g target + 20 lig pBAc102 (supplied by B. Masterson). pBAc102 carries the same genomic transposase sequence as the pNT804 effector but under the control of a double CaMV 35S promoter followed by a synthetic oligonucleotide sequence derived from the 5'-leader of tobacco mosaic virus (Grevelding et al, 1992). pBAc102 was used instead of pNT804 because it does not carry the bacterial ampicillin-resistance gene.…”
Section: Ds Excision Takes P/ace In the Target Plasmidmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Grevelding et al (1992) suggested that a significant prorportion of the Ac transcript in Arabidopsis has a size of around 1.1 kb, and it was hypothesized that this may be due to incorrect processing of the mRNA. We have already demonstrated that intron 4 is alternatively spliced in Arabidopsis but none of the gene products was as small as those found by Grevelding.…”
Section: The Maize Ac Transcript Is Alternatively Polyadenylated In Amentioning
confidence: 99%
“…The majority of work investigating Ac transposition has utilized the genomic sequence as a transposase source rather than the cDNA, as studies comparing the activity of the two suggest that the cDNA is even less active in tobacco than the genomic Ac element (Schofield et aL, 1993). One explanation for reduced AciDs transposition in Arabidopsis could be that Arabidopsis inefficiently processes Ac pre-mRNA (Grevelding et al, 1992;Keller et al, 1992;Swinburne et al, 1992), as previous research has established that introns derived from monocotyledonous (monocot) genes are often aberrantly spliced in dicot plant species ' (Goodall and Filipowicz, 1991;Keith and Chua, 1986), and possibly aberrantly polyadenyated (Keith and Chua, 1986). In this paper we confirm that the maize Ac transposase transcript is both alternatively spliced and prematurely polyadenyl- Primers 'a' span the first two introns (5' anneals from 1047; 3' to position 2671), and primers "b' span the latter two introns (5' anneals to position 3033; 3' at position 4060).…”
Section: Introductionmentioning
confidence: 99%